The impacts of COVID-19 on the environmental sustainability: a perspective from the Southeast Asian region - Praveena, Sarva Mangala (Environ Sci Pollut Res Int, 2021)
This study examined the impacts of the Coronavirus disease 2019 (COVID-19) on the environment in the Southeast Asia region using qualitative content analysis to analyze the textual data of published studies and other online references such as the organizational reports. Besides, the materiality assessment particularly the Global Reporting Initiative was conducted by analyzing short- and long-term impacts from the stakeholders’ (local and regional policymakers) perspective. The positive effects of COVID-19 lockdown and movement restriction on the regional environment identified in this study included a reduction in air pollution, improvement of air and water quality, lower noise levels, and reduced land surface temperature. In contrast, the negative effects encompassed a rise in the use of plastics and the generation of medical waste in Indonesia, Malaysia, Thailand, the Philippines, and Vietnam. Materiality assessment findings have offered insights on the need of stakeholders’ importance for further to deal with huge amount of waste, inadequate waste management facilities and system, explore the effectiveness of such sustainable work and lifestyle changes, utilize real-time monitoring air quality data and future prediction responses for climate change mitigation and adaptation policies as well as consideration towards new green technologies for clean energy in each Southeast Asian country and at regional level. It is anticipated that this study will contribute towards a better understanding of the impacts of COVID-19 on environmental sustainability in the Southeast Asia region, particularly from the perspective of the stakeholders. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11356-020-11774-0.